Utilization of standing waves to improve effectiveness of noise barriers - Wong, Jian Ming (2017)
Noise control has always been crucial in both residential and industrial architecture. Noise control methods often utilize traditional methods of using thick and heavy materials to block out noise. As space constraints limit the effectiveness of traditional noise control methods, other ways to improve the effectiveness of noise control methods were explored. The objective of the project is to study the effects of standing waves to improve the effectiveness of sound barriers. This will help reduce the amount of materials required and also reduce the need for very thick layers of materials, which in turn saves costs and time to construct such structures. By utilizing the concepts of superpositioning of sound waves, the sound waves can be made to cancel each other out by varying the distance between two parallel plates. The results showed that the concept was effective at improving the low-frequency noise reduction by up to 12dB by simply varying the distances between parallel plates. Despite achieving improvement in the lower frequencies, due to the broadband nature of noise sources, there may be other frequencies that are amplified for a particular distance configuration. Nevertheless, the project has provided valuable insights into alternative forms of improving noise reduction of sound barriers.